Curcumin: a calixarene derivative micelle potentiates anti-breast cancer stem cells effects in xenografted, triple-negative breast cancer mouse models - Wei Chen; Lin Li; Xiaofen Zhang; Yuan Liang; Zhijun Pu; Lingfeng Wang; Jingxin Mo (Taylor & Francis Group, 2017)
Triple-negative breast cancer (TNBC) is a heterogeneous and clinically aggressive disease with no approved targeted therapy. Curcumin has shown therapeutic potential against TNBC, but it shows low bioavailability and low efficacy when administered as a free drug. Here we describe a novel vehicle for in vivo delivery of curcumin based on the phosphorylated calixarene POCA4C6. Curcumin-loaded POCA4C6 micelles (CPM) were prepared using the thin-film method and they showed a unilamellar structure with an average particle size of 3.86 nm. The micelles showed high curcumin encapsulation efficiency and loading was based on liquid chromatography-tandem mass spectrometry. Studies with cell cultures suggest that CPM can sustainably release curcumin in a pH-dependent manner. The micelles efficiently inhibited proliferation, invasion, migration and tumor spheroid formation by BT-549 human breast cancer cells. These effects involved increased apoptosis and reduced levels of nuclear β-catenin and androgen receptor. After injection into tumor xenografts, CPM persisted in the tumor tissue and efficiently inhibited tumor growth without causing obvious systemic toxicity. CPM also significantly reduced levels of CD44+/CD133+ breast cancer stem cells. Our results highlight the potential of CPM as an effective therapy against TNBC.